Immersive learner's usability and experience through VMMBG during COVID-19 pandemic: an evidence of a higher educational institution / Shahreena Daud ... [et al.] - Daud, Shahreena; Osman, Idris; Abu Yazid, Zarinah; Md Taib, Norraeffa; Mohd Nor, Amirudin (2021)
In Malaysian Higher Education Institutions (HEIs), digital educational game-based learning is still in its infancy. Educators are urged to use digital games to build and develop educational innovation in order to accomplish learning goals while also boosting learners' motivation, enjoyment, engagement, and experience during the Covid-19 pandemic. This study, therefore measured learners’ usability and experience through Virtual Money Mine Board Game (VMMBG) in the Personal Financial Planning (PFP) course at the Faculty of Business and Management, UiTM Melaka Branch, Melaka City Campus. The VMMBG was played via the Google Meet platform, and nine groups were formed. The MEEGA+ Model elements were used to assess the usability and player experience with VMMBG. The data from the 55 undergraduate students participating in the PFP course was analysed using SPSS. According to the findings, operability was the most essential factor for game players, while aesthetics, learnability, and accessibility piqued their interest and motivated them to complete the difficult tasks on the digital platform. Players found VMMBG, as well as the game's rules, characteristics, and features, to be entertaining and enjoyable. To conclude, VMMBG has proven to be a versatile learning tool for students seeking particular information, engagement, and academic success in the PFP course. Educational games in higher education institutions should be linked to learning objectives to assist learners' knowledge acquisition, cognitive and and soft skill development.